Characterization of a novel HLA‐B*18 variant allele, HLA‐B*18:122, by genome sequencing. (20th October 2016) - Sciarrino, R.; De Donno, M.; Biagini, C.; Rombolà, G.; Curcio, M.
Abstract : The HLA‐B*18:122 allele showed four nucleotide differences from HLA‐B*18:01:01:01 .